2008
DOI: 10.1007/s11999-007-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction

Abstract: The bone-patellar tendon-bone has been widely used and considered a good graft source. The quadriceps tendon was introduced as a substitute graft source for bonepatellar tendon-bone. We compared the clinical outcomes of anterior cruciate ligament reconstructions using central quadriceps tendon-patellar bone and bone-patellar tendonbone autografts. We selected 72 patients who underwent unilateral anterior cruciate ligament reconstruction using bone-patellar tendon-bone between 1994 and 2001 and matched for age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 43 publications
6
101
0
1
Order By: Relevance
“…This autograft shares biological and mechanical properties with other grafts such as the patellar ligament or hamstrings, sometimes with superiority (Han et al 2008). Harvesting the quadriceps tendon (with or without patellar bone) might have an impact on the function of the extensor apparatus of the knee joint as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…This autograft shares biological and mechanical properties with other grafts such as the patellar ligament or hamstrings, sometimes with superiority (Han et al 2008). Harvesting the quadriceps tendon (with or without patellar bone) might have an impact on the function of the extensor apparatus of the knee joint as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that the ACL reconstruction with BPTB autograft produced good clinical results (Harner et al, 1996;Fu et al, 2000;Deehan et al, 2000;Gorschewsky et al, 2007;Han et al, 2008). However, a desire to avoid the sacrifice of autologous tissue and to minimize surgical trauma and postoperative donor site morbidity has promoted the consideration of alternative graft sources (Stringham et al, 1996;Siebold et al, 2003;Barrett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been retrospective studies that compared QTPB and BPTB morbidities following ACLR. 13,14 The outcomes of these studies demonstrated similar graft failure rates, 13,14 and similar flexion/extension deficits. 13 However, increased anterior knee pain and donor site morbidity was greater for individuals who underwent BPTB compared with the QTPB group.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 70%
“…However, two retrospective studies that were not included in the CAT compared subjective patient-reported outcomes between BPTB and QTPB patients. 13 The results indicated no significant differences in Lysholm scores when compared postoperatively (BPTB = 92.8, QTBP = 91.5 13 ; BPTB = 95, QTBP = 94 14 ). Additional clinician-based outcomes were also measured in each of the studies, including laxity/ anteroposterior translation, [3][4][5][6] knee function using ROM 3,6 and one-leg hop index, 3 patellofemoral crepitus, 3 thigh girth, 4 muscle strength, 4,6 joint space narrowing, 4 anterior knee pain, 6 and the IKDC guidelines were used during physical examination.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 86%